Whole genome shotgun sequences for microsatellite discovery and application in cultivated and wild Macadamia (Proteaceae)1. (31st March 2014) - Nock, Catherine J.; Elphinstone, Martin S.; Ablett, Gary; Kawamata, Asuka; Hancock, Wayne; Hardner, Craig M.; King, Graham J.
Abstract : Premise of the study: Next‐generation sequencing (NGS) data are widely used for single‐nucleotide polymorphism discovery and genetic marker development in species with limited available genome information. We developed microsatellite primers for the Proteaceae nut crop species Macadamia integrifolia and assessed cross‐species transferability in all congeners to investigate genetic identification of cultivars and gene flow. Methods and Results: Primers were designed from both raw and assembled Illumina NGS paired‐end reads. The final 12 microsatellite markers selected were polymorphic among wild individuals of all four Macadamia species— M. integrifolia, M. tetraphylla, M. ternifolia, and M. jansenii —and in commercial macadamia cultivars including hybrids. Conclusions: We demonstrate the utility of raw and assembled Illumina NGS reads from total genomic DNA for the rapid development of microsatellites in Macadamia . These primers will facilitate future studies of population structure, hybridization, parentage, and cultivar identification in cultivated and wild Macadamia populations.